Training on the Use of Montessori-Based Mathematics Learning Media for Primary and Secondary School Teachers in Thousand Islands - Haeruman, Leny Dhianti; Aziz, Tian Abdul; Hidajat, Flavia Aurelia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Learning media has an important role in learning mathematics because mathematics is an abstract science and requires a deep understanding of concepts. Students have difficulty in understanding mathematics due to the teacher's monotonous explanation in class without any learning media or epraga tools. Fun learning media is interactive learning media, which allows students to use the media themselves and interact both with other students and with teachers. One example of interactive learning media is Montessori learning media. Based on observations at partner locations, it was found that mathematics teachers in elementary and secondary schools have never used Montessori learning media, therefore training on the use of Montessori-based learning media is needed for elementary and secondary school teachers so that classroom learning runs optimally in accordance with learning objectives. Training on the use of Montessori-based learning media has a positive impact on teachers, it can be seen from the final questionnaire of the training participants provide positive feedback, to this training activity, namely with data interpretation of 96%.